Kompolan sebagai Sarana Pendidikan Agama di Masyarakat Madura - Jauharotul Makniyah; Malatus Sa'adah (Maharot : Journal of Islamic Education, 2020)
This article aims to describe the experiences and feelings of members of the majlis taklim and the meaning of religious activities in the majlis taklim. The approach used in this research is a qualitative research with a phenomenological study type. While the data collection techniques in this study were interviews, observation, and documentation. Sources of data used in this study primary and secondary data. Data analysis of this research is data reduction, data display and verification or conclusion. The results of the study show as follows: The experience of members of the taklim majlis is gaining knowledge and knowledge by attending the taklim majlis in umdatul khairat can be taught some knowledge, making new friends from various hamlets so that they can meet each other and gather together by attending the ta' majlis The lim, has time to recite the yasin and tahlil together and remember our elders together, stay in touch with the teachers and friends with the majlis taklim being able to stay in touch with the nyai. The feelings felt by the members of the majlis taklim were very happy and enthusiastic in participating in the activities in the majlis taklim 'Umdatul Khairat.